Recent Development Strategies for Bismuth‐Driven Materials in Sustainable Energy Systems and Environmental Restoration. Issue 10 (16th December 2022) - Adhikari, Sangeeta; Mandal, Sandip; Kim, Do‐Heyoung
Abstract: Bismuth(Bi)‐based materials have gained considerable attention in recent decades for use in a diverse range of sustainable energy and environmental applications due to their low toxicity and eco‐friendliness. Bi materials are widely employed in electrochemical energy storage and conversion devices, exhibiting excellent catalytic and non‐catalytic performance, as well as CO2 /N2 reduction and water treatment systems. A variety of Bi materials, including its oxides, chalcogenides, oxyhalides, bismuthates, and other composites, have been developed for understanding their physicochemical properties. In this review, a comprehensive overview of the properties of individual Bi material systems and their use in a range of applications is provided. This review highlights the implementation of novel strategies to modify Bi materials based on morphological and facet control, doping/defect inclusion, and composite/heterojunction formation. The factors affecting the development of different classes of Bi materials and how their control differs between individual Bi compounds are also described. In particular, the development process for these material systems, their mass production, and related challenges are considered. Thus, the key components in Bi compounds are compared in terms of their properties, design, and applications. Finally, the future potential and challenges associated with Bi complexes are presented as a pathway for new innovations. Abstract : Bismuth (Bi)‐based materials have gained considerable attention in recent decades for use in a diverse range of sustainable energy and environmental applications due to their low toxicity and eco‐friendliness. In this review, a comprehensive overview of the properties of individual Bi material systems and their use in a range of applications is provided.